The Role, Responsibilities, and Professionalism of Muslim Teachers in Enhancing Educational Quality - Tanjung, Rizky Syahridun (Yayasan Bayt Shufiya Nusantara, 2024)
This article aims to critically examine the role, responsibilities, and professionalism of educators through a literature-based approach. The study reviews a wide range of relevant sources including academic literature, national education policies, and prior research findings to construct a comprehensive understanding of the dynamics of the teaching profession in Indonesia. The findings indicate that teacher professionalism is shaped not only by academic qualifications but also by integrity, commitment, and the ability to adapt to changing times. The article highlights the importance of continuous capacity-building for teachers, as well as the need for regulatory and institutional support to uphold the dignity of the teaching profession. These findings are expected to serve as a reference for policymakers in formulating education policies that prioritize the improvement of teacher quality and the overall advancement of national education.